Incumbent vs Challenger: A Comparative Study of Political Power in the 2020 Regional Head Election in Karimun Regency: Petahana vs Penantang: Studi Perbandingan Kekuatan Politik Pada Pemilihan Kepala Daerah di Kabupaten Karimun Tahun 2020 (Journal of Political Issues, 2023)
Only two pairs of candidates ran for Karimun Regent and Deputy Regent in the 2020 Karimun Regional Election. In this election, there was a uniqueness in that the incumbent pair supported by the "fat" coalition with such big campaign finances were unable to dominate the vote and were nearly defeated by the challenger pair sponsored by the "lean" coalition and far lesser campaign funds with a difference of only 86 votes. This study is qualitative research employing a comparative qualitative approach. Interviews and documentation were used to acquire data. In this study, qualitative data analysis techniques using interactive models were employed to describe the situation. According to the findings of this study, the incumbent couple won the 2020 Karimun Regent election by a difference of only 86 votes. This cannot be separated from the role of political forces held by each candidate couple. The most significant distinction between the two pairs of candidates for Karimun Regent and Deputy Regent in 2020 is that the incumbent pair has only four political powers, including NGOs, political parties, mass media, and business groups. Meanwhile, the challengers are supported by six political powers: NGOs, political parties, labor organizations, mass media, pollsters, and the bureaucracy.
Keywords: Comparison; Election; Political Power